Risk of serious COVID-19 outcomes among adults and children with moderate-to-severe asthma: a systematic review and meta-analysis. (2nd November 2022) - Lee, Bohee; Lewis, Grace; Agyei-Manu, Eldad; Atkins, Nadege; Bhattacharyya, Urmila; Dozier, Marshall; Rostron, Jasmin; Sheikh, Aziz; McQuillan, Ruth; Theodoratou, Evropi
Background: The Joint Committee on Vaccination and Immunisation in the United Kingdom requested an evidence synthesis to investigate the relationship between asthma and coronavirus disease 2019 (COVID-19) outcomes. Objective: We conducted a systematic review and meta-analysis to summarise evidence on the risk of severe COVID-19 outcomes in people with uncontrolled asthma or markers of asthma severity. Methods: High-dose inhaled corticosteroids (ICS) or oral corticosteroids (OCS) were used as markers of asthma severity, following international or national asthma guidelines. Risk of bias was assessed using Joanna Briggs Institute tools. Adjusted point estimates were extracted for random-effects meta-analyses and subgroup analyses. Results: After screening, 12 studies (11 in adults and one in children) met the eligibility criteria. Adults using high-dose ICS or OCS had a pooled adjusted hazard ratio (aHR) of 1.33 (95% CI 1.06–1.67, I 2 =0%) for hospitalisation and an aHR of 1.22 (95% CI 0.90–1.65, I 2 =70%) for mortality for COVID-19. We found insufficient evidence for associations between markers on COVID-19 mortality in the subgroup analyses. Conclusions: Adults with severe asthma are at increased risk of COVID-19 hospitalisation compared to nonusers. Our analysis highlighted the dearth of studies in children with asthma investigating serious COVID-19 outcomes. This systematic review demonstrated that adults with severe asthma requiring high-dose inhaled corticosteroids or oral corticosteroids have a higher risk of hospitalisation from COVID-19 than those with mild asthma or no asthma. https://bit.ly/3zYiWaO